THE VIOLATION MAXIM OF STUDENT IN FACULTY OF FOREIGN LANGUAGES, MAHASARASWATI DENPASAR UNIVERSITY - I Gusti Ayu Vina Widiadnya Putri; Ida Bagus Gede Nova Winarta (Universitas Pendidikan Ganesha, 2021)
The research is aimed to analyze the maxims violations committed by students of the English study program, Faculty of Foreign Languages, Mahasaraswati Denpasar University. All speakers and interlocutors may not understand well the intent and purpose of utterance. Some utterances may contain different aims and objectives from the statement or question of the other person. To determine the suitability and misunderstanding of speech between listeners and speakers, Grice (1975) has initiated a theory of cooperation principles by classifying them into four types. This research is a qualitative descriptive study by collecting data by observation, note taking and recording. The result of this research is violations of maxims have occurred in students' speech. The four violations of maxims were found here. Students violate the maxim of quantity, maxim of quality, maxim of relevance and maxim of method. The most dominant violation of maxims is a violation of the maxims of quantity.